The Characteristics of Vegetation, Soil and Carbon Reserves in Mine Area of Mount Pongkor, Bogor, West Java KARAKTERISTIK VEGETASI DAN CADANGAN KARBON PADA LAHAN TAMBANG DI GUNUNG PONGKOR, BOGOR, JAWA BARAT - Entin Kartini; Lailan Syaufina; Irdika Mansur (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
This research was conducted in the undisturbed land, underground mining area and illegal mine (PETI) land of Mount Pongkor. This research is aimed to analyze the difference of structure and composition of vegetation, and to predict carbon reserves above soil surface in undisturbed land, underground and PETI, so then adaptive type of vegetation can be identified. This study was conducted by using simple random sampling method with 40 plots. Estimation of carbon stocks using non- destructive method according ISO 7742 2011. The results show that structure and composition between underground is same as undisturbed land with complete stratification which consists of bushes, seedling, pole, trees, liana and epifit, while PETI land has no complete stratification. In PETI land, it’s only found one type of vegetation on pole level that is Vernonea arborea while trees is not found. The species Syzygium lineatum, Lithocarpus sp, Maesopsis eminii, Altingia excelsa, and Ziziphus mauritiana are the species with highest Important Value Index (IVI) in undisturbed land. The Species M eminii, Lithocarpus sp, Altingia excelsa, Vernonea arborea, and Castanopsis argentea are the highest in underground area, so that they are the most dominant species in that location. Species Diversity Index (H’) in undisturbed land is between 1.28-2.62 (medium), while in underground are is between 1.93-2.88 (medium), and in PETI land is between 0-2.45 (very low to medium). Index of Species Richness (R) in undisturbed land and underground on every level of vegetatation is between 1.74-5.9, while in PETI land is lower than 3.5 (very low). Similarity Index (E) in research sites on every level of vegetation is between 0.58-0.98 (relatively uniform), except in PETI land for pole level and trees, the value of E is zero. The potency of carbon stock in undisturbed land was about 288.94 tons C/ha and 192.74 ton C/ha for underground area, whereas was about 0.06 tons C/ha was found in PETI location.Key words: llegal mining, underground mining, suspected carbon stocks, vegetation